FAKULTATYWNA MEDIACJA W PROCESIE O ROZWÓD WEDŁUG ZNOWELIZOWANEGO KODEKSU POSTĘPOWANIA CYWILNEGO - Stojanowska, Wanda (Zeszyty Prawnicze, 2017)
Optional Mediation in the Divorce Proceedings as an Effect of the Amendments to the Code of Civil Proceedings Summary The article discusses the provisions amending the Code of Civil Proceedings with respect to the conciliatory proceedings with regard to a divorce. The amendment consists in a removal of the obligatory conciliatory proceedings and introduction of a new procedural means - mediation. The author evaluates the amendments and draws critical conclusions. First, the removal of the conciliatory proceedings was not right. It should have been retained treating it together with mediation as supplementary means. At present the court cannot encourage the parties to use mediation because it is obliged to appoint a sitting and commencing the proceedings for revealing evidence. Moreover, mediation is optional, therefore, it is probable that it will not be used in practice.